Implementing the Role of Civil Servants as the Binding Force and Unifying Element of the Nation within the Surabaya City Government - Abdul Hakim; Arief Rachmat Fauzi; Aris Fajari Teguh Nugroho; Yacinta Stefila Paramawati; Ika Trisnasari (Catalist Indo Publisher, 2026)
Background Civil servants play a strategic role not only as implementers of public policy and providers of public services, but also as the glue that binds and unites the nation. This study aims to analyze the implementation of the civil servants’ role as the glue that binds and unites the nation within the Surabaya City Government. Methods This study employs a descriptive method with a qualitative approach through literature review and interviews with employees within the Bakesbangpol and the Organization Division of the Surabaya City Government. Analysis was conducted using a top-down policy implementation approach to assess the extent to which local government policies and programs are translated into practical implementation on the ground. Results The findings indicate that the implementation of civil servants’ roles in Surabaya has been carried out systematically. This implementation demonstrates that civil servants not only perform administrative functions but also act as agents of social change, contributing to strengthening social cohesion and maintaining national unity at the local level. Conclusions The implementation of the role of ASN as a unifying force for the nation within the Surabaya City Government has been carried out systematically and supported by various cross-sectoral collaborative programs. ASN not only perform administrative functions but also act as agents of social change in strengthening social cohesion and national values within the community.